The Effect of Features and Product Quality on Vivo Smartphone Purchase Decision at Faizal Cell Kaur District - Imam Mas’ud; Ida Anggriani; Yanto Effendi (Penerbit Jurnal Indonesia, 2021)
The purpose of the study was to determine the effect of product quality and features on consumers purchasing decisions for Vivo Smartphones at Faizal Cell, Kaur Regency. The sample in this study were 150 consumers who purchased Vivo Smartphone at Faizal Cell, Kaur Regency who were taken by using accidental sampling technique. The data then collected by using a questionnaire and analyzed through multiple linear regression, determination test and hypothesis testing. The results of the regression analysis show Y = 18.944 + 0.317X1 + 0.242 X2 + 2.688, that showed a positive regression direction. It means that there is a positive influence between X1 (features) and X2 (product quality) on purchasing decisions (Y). If the variable features and product quality increase, it will increase purchasing decisions. Moreover, the magnitude of the coefficient of determination is 0.343 showing that X1 (features) and X2 (product quality) affect purchasing decisions (Y) by 34.3% while the remaining 65.7% is influenced by other variables not examined in this study. Likewise, the results of the t test at a significance level of 0.05 explained that partially the feature and product quality variables had a significant influence on the purchasing decision variables of Faizal Cell, Kaur Regency. Finally, the results of the F test at a significance level of 0.05 explain that the variable features and product quality have a simultaneous effect on purchasing decisions at Faizal Cell, Kaur Regency